55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0334
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Response of Bird-Damaged Fan Blades Using a Coupled CFD/CSD Framework

Abstract: The aeroelastic response of a bird-damaged fan stage at the inlet of a high-bypass ratio turbofan engine is examined using a combined CFD/CSD model. ANSYS CFX is used for the computational fluid dynamic (CFD) calculations combined with the ANSYS Multifield (MFX) solver that couples ANSYS CFX with ANSYS Mechanical APDL to perform aeroelastic response calculations. The damaged fan sector consists of 5 blades that represent the geometry resulting from a numerical bird strike simulation. The forced response of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…28, and it was concluded that the "coarse" mesh identified in Ref. 28 is sufficiently accurate for the objectives of the current study. The ANSYS TurboGrid ATM topology is not applicable for full wheel geometries that include a set of damaged blades.…”
Section: Referred Mass Flowmentioning
confidence: 80%
See 4 more Smart Citations
“…28, and it was concluded that the "coarse" mesh identified in Ref. 28 is sufficiently accurate for the objectives of the current study. The ANSYS TurboGrid ATM topology is not applicable for full wheel geometries that include a set of damaged blades.…”
Section: Referred Mass Flowmentioning
confidence: 80%
“…Mesh sensitivity studies were conducted in Ref. 28, and it was concluded that the "coarse" mesh identified in Ref. 28 is sufficiently accurate for the objectives of the current study.…”
Section: Referred Mass Flowmentioning
confidence: 99%
See 3 more Smart Citations